All hands on deck : a modern-day high seas adventure to the far side of the world - Sofrin, Will (Abrams Press, 2023)
"A maritime adventure memoir that follows a crew of misfits hired to sail an 18th-century warship 5,000 miles to Hollywood"--Amazon.